PEMBELAJARAN GERAK SENAM BER-IRAMA DAPAT MENINGKATKAN KECERDASAN KINESTETIK TK ABA 3 SUMBERSARI - Bahtiar Hari Hardovi; Misyana Misyana; Ahmad Bahriyanto; Dinda Putri Toyibah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2020)
Early childhood Education (Paud) is one of the satu efforts to improve its physical, cognitive, social, spiritual and emotionalchanges. TK ABA III located in the village of kelurahan sumbersari, jember District is the educational place for children . Every Schooling definitely There are no a prob growingissues. The problems of the school ABA 3 Sumbersari Kindergarten school through interviews with the headmaster , Mrs . Erna Sri Rahayu., S. Pd menutit: First, the manpower of lack of rhythmic gymnastics knowledge . Second Lack of knowledgeable bahwasanya The watering gymnastics can improve kinesthetic. With a thus Required implementation of Empowerment pelatihan RHYTHM training in Kindergarten School ABA 3 Sumbersari. Then need to be adanya of pelatihan Gymnastics training is rhythmic to the ada education Personnel in lingkungan TheSchool environment. In the Skeletal pengembangan Model development and teknologi Learningtechnology. Then Teams Devotion Deliver Training rhythmic motion of Gymnastics . Includes a step foot motion technique that needs to be noticed by the participants, then participants follow and memorize and perform the movement repeatedly. Then the sculpte gives the technique of arm swing and the Pesesrta to perform repeatedly. And the last participant performs the movement in a rhythm. With a rhythmic gymnastics training the teachers become aware of the rhythmic gymnastics that is bungan by increasing the Kinestetian intelligence of early childhood.